Risk of undiagnosed infection in men attending a sexual assault referral centre. Issue 6 (30th November 2004) - Reeves, I; Jawad, R; Welch, J
Abstract : Objectives: To investigate men undergoing forensic examination at the Haven, a specialist centre for the management of sexual assault in south London. Methods: Forensic notes of 92 men attending the Haven from May 2000 to August 2003 were identified and a detailed review performed. Results: Males ranged in age from 12 to 51 years, with 83% within the range 12–35 years. 78% were white. Of those who were sexually active (n  =  82) 30% were heterosexual, 34% were homosexual, and the remainder provided no information regarding sexual orientation. Most clients were referred by the police (n = 79) and attended within 3 days of the alleged assault (n = 73). Many of the victims had increased vulnerability to assault—for example, through alcohol or drug consumption or mental health difficulties. One assailant was reported in 61 cases but two or more assailants in 26. Women were reported as assailants in four cases. The sexual assault was frequently accompanied by other physical assault (n = 45). Use/threat of a weapon was reported in 18 cases. Rape or attempted rape was reported in 59 cases and was the most common assault. Non-genital injuries were documented in 37 men (40%). Anal injuries were seen in 31 (34%). The non-attendance rate at follow up was 41%. Post-exposure prophylaxis (PEP) against HIV was commenced in 31 men (34%). 23 of the 54 men (43%) reporting rape and 14 of the 31 (45%) with anal injuries initiated PEP. Conclusions: The number of men presenting after sexual assault is likely to increase but despite significant risk many do not engage with medical care. This carries an unknown risk of HIV and other STI transmission.